Methodical model of professional communication training of students on the English lessons - Gulnara F. DulmukhametovaSvetlana E. Nikitina, Мarina N. Vinnikova,; Pavitskaya, Zoya I. (Opción, 2019)
The article reviews the structure and the content of the methodological model of professional communication teaching of students of humanitarian specialities on the English lessons. A methodological model of professional communication training of students of humanitarian specialities on the English lessons was developed. It has the following structure: logical-methodological, psychological-didactic and technological component. In conclusion, the proposed methodological model is an attempt to weaken the contradictions between the objective necessity of teaching professional communication of students of humanitarian profile in English classes and the insufficient elaboration of this problem, both theoretically and methodically.